Rasionalisasi Pos Curah Hujan Menggunakan Metode Kagan di DAS Ciliwung untuk Operasi Bendungan Ciawi dan Sukamahi - Propezite Nurhutama Mustain; Dyah Ari Wulandari; Hari Nugroho; Suripin Suripin (Universitas Islam 45, 2023)
Hydrological stations are an important element in order to provide preliminary information to dam managers in planning and managing dams. Rainfall data generated from rainfall stations is one of the inputs in hydrological analysis that can be used in dam management. To support the hydrological analysis, an appropriate network of rainfall stations is needed, both in terms of the number and location of rainfall stations. Therefore, it is necessary to study the rationalization of the hydrological station network within the Ciliwung Watershed, so that it can be utilized in dam operations. The purpose of this study is to obtain an efficient and effective network of rainfall stations in the Ciliwung watershed to support the operation of the Ciawi and Sukamahi Dams. In this case, the Kagan method was used in the analysis of the rationalization of the rainfall station network by producing the optimum number of rainfall stations in the Ciliwung watershed, that is 29 rainfall stations. Based on these results, the number of rainfall stations in the Ciliwung watershed has met in terms of number, but the location point needs to be adjusted to the Kagan triangle.